Physicochemical Properties of Chicken Nuggets with Various Types of Flour Substitutes and Carrot Addition - A. A. Simollah; H. Hikmah; M.I. Said (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2026)
This study aimed to analyze the effect of using wheat flour, breadfruit flour, and a combination of both, as well as the addition of carrots, on the quality of chicken nuggets. This study was conducted in two experimental stages using a Completely Randomized Design (CRD). Stage I used a 3x4 factorial RAL pattern with 3 repetitions. Factor A (Type of flour) consisted of wheat flour (X), a mixture of wheat flour and breadfruit flour (Y), and breadfruit flour (Z). Factor B (flour level) included 7.5%; 15%; 22.5%; and 30%. Stage II used a single-factor RAL with four treatments of carrot addition levels (P): 7.5%; 15%; 22.5%; and 30%, each repeated three times. The research parameters included cooking loss, meat shear force, and water holding capacity (stage I) as well as cooking loss, meat shear force, water holding capacity, dietary fiber, and β-carotene (stage II). Phase I research showed that the type and level of flour had a very significant effect (P<0.05) on water holding capacity and meat shear force. The use of 15% breadfruit flour and 30% carrot gave the best results in cooking loss (5.00%), β-carotene (245.13 µg/100g), and dietary fiber (5.82%). Keywords: Nuggets, breadfruit flour, carrots, physicochemical properties